Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.3109/15412555.2015.1041102
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Airflow Obstruction in a Black African Population: Results of BOLD Study, Ile-Ife, Nigeria

Abstract: Measurements and main results: The prevalence of a reduced FVC was 70.4% for men and 72.8% for women when using NHANES values for white Americans, 17.8% for men and 14.4% for women using NHANES equations for African Americans and 15.5% and 20.5% for men and women respectively using the GLI 2012 equations. Using the equations derived from non-smoking respondents in the survey without a respiratory diagnosis, the prevalence of a reduced FVC was <4% for both men and women. FVC was lower in participants with <7 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
34
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 44 publications
8
34
2
Order By: Relevance
“…The absence of a relationship between biomass exposure and airway obstruction may be explained by limited study power related to the low prevalence of moderate to severe obstruction (3.6%), or misclassification of self-reported rather than objectively quantified biomass exposure, but it is consistent with findings of a recent population-based study in Nigeria (31,32). In the case of tobacco, it may also reflect a low intensity of exposure in this setting, which was insufficient to produce significant levels of clinically important COPD; smoking prevalence was limited and pack-year exposure was low.…”
Section: Discussionsupporting
confidence: 78%
“…The absence of a relationship between biomass exposure and airway obstruction may be explained by limited study power related to the low prevalence of moderate to severe obstruction (3.6%), or misclassification of self-reported rather than objectively quantified biomass exposure, but it is consistent with findings of a recent population-based study in Nigeria (31,32). In the case of tobacco, it may also reflect a low intensity of exposure in this setting, which was insufficient to produce significant levels of clinically important COPD; smoking prevalence was limited and pack-year exposure was low.…”
Section: Discussionsupporting
confidence: 78%
“…Similarly, Mukherjee et al 27 compared 681 non-smoking women from eastern India who cooked exclusively with biomass (wood, dung and crop residues) with 438 age-matched women from similar neighbourhoods who cooked with liquefied petroleum gas (LPG) and reported that airflow obstruction was diagnosed in 4.6% of biomass users, as compared with only 0.9% of LPG users. In contrast, Obaseki et al 28 reported that there was no association between chronic airway obstruction and the use of firewood or coal for cooking or heating in Nigeria. The reported biomass exposure domestically might have been under-reported by the participants, considering social desirability.…”
Section: Discussionmentioning
confidence: 93%
“…Previous literature has described the details of recruitment (20). Figure 1 illustrates the key aspects of the recruitment process.…”
Section: Resultsmentioning
confidence: 99%